PERCERAIAN ASN DI PENGADILAN AGAMA PERSPEKTIF TOKOH-TOKOH NAHDLATUL ULAMA - Achmad Amin; Fathurrahman Alfa; Syamsu Madyan (Jurnal Hikmatina, 2021)
The study entitled Divorce of State Civil Apparatus / Civil Servants in the Religious Courts Perspective of Nahdlatul Ulama Figures discussed three problem formulations, namely the requirements for ASN divorce according to KHI, views of NU figures on the requirements for ASN divorce in KHI, conflicts and the impact of differences that occur in ASN divorce cases in the Religious Courts Between the views of KHI and NU figures.The method used in this research is a qualitative research with a descriptive type of research. Data collection techniques used are observation, interviews, and documentation. Based on this research, the results of the study show that, first, the main requirement in the ASN/PNS divorce procedure is to file a divorce lawsuit with the superior or the authorized party. Second, NU figures prefer to use the basis of Islamic law as legal divorce is the divorce that is pronounced by a husband to his wife, even if it is serious or joking. Third, there is a difference of opinion regarding the ASN/PNS divorce procedure between the Islamic Law Compilation and NU figures due to the lack of socialization of the ASN/PNS divorce law.